Peningkatan Produktivitas Sapi Potong Melalui Introduksi Pakan Konsentrat Dengan Bahan Lokal Pada Masyarakat Asli Papua: Productivity Improvement of Beef Cattle through the Introduction of Feed Concentrates to the Local Papuan - Andoyo Supriyantono; Deny Anjelius Iyai; Abdul Rahman Ollong (IGKOJEI: Jurnal Pengabdian Masyarakat, 2020)
ABSTRACT Beef cattle is one of the livestock which is considered as a side-business by Papuan. Generally, the farming practice is extensive - they let the cattle graze freely in palm plantations or just tie them down around the house. In the last seven years, more Papuan were keeping beef cattle since the government introduced beef cattle to act as a dowry for weddings to the community. The purposes of this community service program-community empowerment learning (KKN-PPM) were (1) Optimal use of agricultural waste such as tofu waste, rice bran, cocoa peels, cassava along with its by-products as additional feeds of beef cattle; (2) Reduced dependence on an additional feed from factories. KKN-PPM was carried out in Waseki Pop, Prafi District for 67 days. KKN-PPM was commenced from provisioning to students concerning the potential of feeding; the development of feed technology; complete feed and feed concentrate. Local feed materials for making feed concentrate were rice brand (70%), stacks (16%0), the waste product of tofu (11%), salt (2%), and urea (1%). Those compositions have met the requirements of dry matter and crude protein for beef cattle. 30 students from different field studies joined the KKN-PPM program. The workload of each student was calculated based on the effective working time (EWT) which was about 288 EWT. The method of implementing KKN-PPM starts from debriefing students on campus, namely the use of potential feed; feed technology development; complete feed and concentrate. During the implementation in the field, students and their supervisors conducted technical guidance on beef cattle maintenance, concentrate processing techniques, and counseling for cattle breeders. During the KKN-PPM activities, a total of 114.4 kg of concentrate was given to 7 cows. Sustainability of the program would be reached when the government of West Papua and Manokwari district had the same program for students every year to make feed concentrate for farmers. Keywords: Feed concentrate; Local material feed; Beef cattle ABSTRAK Sapi merupakan salah satu ternak yang dijadikan usaha sambilan bagi penduduk asli Papua. Pola pemeliharaan sapi pada umumnya dilakukan secara ekstensif yaitu sapi dibiarkan berkeliaran di perkebunan kelapa sawit atau diikat di sekitar rumah. Tujuh tahun terakhir ini, masyarakat asli Papua banyak mengusahakan sapi potong setelah Bupati Manokwari dengan kesepakatan Lembaga Masyarakat Adat memperkenalkan sapi potong sebagai salah satu bentuk mas kawin. Tujuan dilaksanakan Kuliah Kerja Nyata Pembelajaran Pemberdayaan Masyarakat (KKN-PPM) adalah 1. pemanfaatan secara optimal limbah pertanian untuk pakan tambahan sapi potong; 2. Berkurangnya ketergantungan pakan tambahan dari pabrik. KKN-PPM dilaksanakan selama 67 hari di Kampung Waseki Pop Distrik Prafi. Kegiatan ini diikuti oleh 30 mahasiswa secara terpadu dari berbagai bidang ilmu. Volume pekerjaan setiap mahasiswa dihitung berdasarkan Jam Kerja Efektif Mahasiswa yakni sebanyak 288 JKEM. Metode pelaksanaan KKN-PPM dimulai dari pembekalan mahasiswa di kampus yaitu pemanfaatan bahan pakan potensial; pengembangan teknologi pakan; pakan komplit dan konsentrat. Dalam pelaksanaan di lapang, mahasiswa bersama-sama dosen pembimbing melakukan bimbingan teknis pemeliharaan sapi potong, teknik membut konsentrat dan penyuluhan kepada peternak sapi. Konsentrat dibuat dari bahan-bahan lokal setempat yaitu dedak padi (70%), onggok (16), ampas tahu (11%), garam (2%) dan urea (1%). Dengan formulasi konsentrat seperti tersebut maka kebutuhan bahan kering dan protein kasar sapi potong telah memenuhi standar. Selama kegiatan KKN-PPM, total konsentrat yang dibuat sebanyak 114,4 kg yang diberikan pada 7 ekor sapi. PEMDA Provinsi Papua Barat dan Kabupaten Manokwari diharapkan mempunyai program yang sama setiap tahunnya untuk mendanai kegiatan pendampingan dalam pembuatan konsentrat pada wilayah-wilayah binaannya. Kata kunci: Konsentrat; Bahan lokal; Sapi potong